Himbauan Bahaya Pemasangan Bendera di bawah Jaringan Listrik PLN - Irwanto, Tito; Prabowo, Devo; Desita, Ridha Tri; Afriani, Sulisti; Putri, Lydia Gustina (Jurnal Dehasen Mengabdi, 2023)
An electrical grid is an interconnected network for electricity delivery from producers to consumers. Electrical grids vary in size and can cover whole countries or continents. It consists of power stations, electrical substations, electric power transmission, and electric power distribution An electrical grids are very vulnerable to attacks or sabotage, so it is necessary to secure power grids. With more and more computers being used to manage electricity grids, cyberattacks have also started to become a security risk. This problem can be overcome by carrying out socialization to appeal to the dangers of the PLN electricity network, as the title above calls for the danger of placing a flag under the PLN electricity network, it is very dangerous for the occurrence of these problems, an understanding of security and safety is also important for the community. The goal of this service is to provide education or call for notification not to put flags under the PLN electricity network for the safety of the community. At the end of the meeting, a joint evaluation was carried out so that the community could understand.